Health Policy Gaps in Addressing Gender-Based Violence in South African Higher Education Institutions - Tlou, Kagiso Nichoals; Mofokeng, Jacob Tseko (Department of Public Administration, 2025)
Acts of gender-based violence and femicide (GBVF) are among the most common forms of violence in Higher Education Institutions (HEIs) in South Africa and are estimated to affect the lives, health and wellbeing of many people. The scourge of GBVF has in numerous studies and statistics shown to be on the rise. This paper has been conducted to assess the impact of GBVF attacks. A comprehensive search was undertaken for GBVF in HEIs research conducted and published between 2013 and 2023. Literature indexes in various databases were searched. Search terms were GBVF, health, healthcare, and higher education. The meta-analysis approach was used to conduct the methodological review. A sample of 38 research articles and 5 reports that met the inclusion criteria were analysed. A systematic iterative method was employed to extract and reduce the data to draw conclusions. The findings highlighted that GBVF attacks do not affect a person physically only, but they also affect a person’s emotions and health. Becoming aware of factors contributing to access to access to health care services and strategies to address challenges can minimise the occurrence of GBVF in HEIs. Contribution: understanding the impact of GBVF attacks can reduce such attacks.